Need help simplifying this Boolean expression
Clash Royale CLAN TAG#URR8PPP
up vote
1
down vote
favorite
From my textbook, by using distributive law, its able to simplify:
$[(p land lnot q) lor (p land q)] land q$
To:
$[p land (lnot q lor q)] land q $
I don't know how to get to this step, and here is how I've tried by distributing the first expression :
$[(p lor p) land (p lor q) land (lnot q lor p) land (lnot q lor q)] land q$
If I try continue to expand this, it will become very complex. I think I'm doing this in the wrong way and I will appreciate it very much if anyone can explain how the textbook got the simplified answer.
Thanks
logic propositional-calculus
add a comment |Â
up vote
1
down vote
favorite
From my textbook, by using distributive law, its able to simplify:
$[(p land lnot q) lor (p land q)] land q$
To:
$[p land (lnot q lor q)] land q $
I don't know how to get to this step, and here is how I've tried by distributing the first expression :
$[(p lor p) land (p lor q) land (lnot q lor p) land (lnot q lor q)] land q$
If I try continue to expand this, it will become very complex. I think I'm doing this in the wrong way and I will appreciate it very much if anyone can explain how the textbook got the simplified answer.
Thanks
logic propositional-calculus
add a comment |Â
up vote
1
down vote
favorite
up vote
1
down vote
favorite
From my textbook, by using distributive law, its able to simplify:
$[(p land lnot q) lor (p land q)] land q$
To:
$[p land (lnot q lor q)] land q $
I don't know how to get to this step, and here is how I've tried by distributing the first expression :
$[(p lor p) land (p lor q) land (lnot q lor p) land (lnot q lor q)] land q$
If I try continue to expand this, it will become very complex. I think I'm doing this in the wrong way and I will appreciate it very much if anyone can explain how the textbook got the simplified answer.
Thanks
logic propositional-calculus
From my textbook, by using distributive law, its able to simplify:
$[(p land lnot q) lor (p land q)] land q$
To:
$[p land (lnot q lor q)] land q $
I don't know how to get to this step, and here is how I've tried by distributing the first expression :
$[(p lor p) land (p lor q) land (lnot q lor p) land (lnot q lor q)] land q$
If I try continue to expand this, it will become very complex. I think I'm doing this in the wrong way and I will appreciate it very much if anyone can explain how the textbook got the simplified answer.
Thanks
logic propositional-calculus
logic propositional-calculus
edited Sep 9 at 0:16


amWhy
190k26221433
190k26221433
asked Sep 8 at 23:52


IhavelowIQ
616
616
add a comment |Â
add a comment |Â
2 Answers
2
active
oldest
votes
up vote
2
down vote
accepted
The Distributive law goes both ways, because it is an equivalence.
That is, using the Distributive Law you can go from $p land (neg q lor q)$ to $(p land neg q) lor (p land q)$, but you can use that same Distributive Law to go from the latter to the former, and that is what they did here.
I believe the name is somewhat to blame for the fact that so many students, like you, only think of the Distributive Law going one way, because going from $(p land neg q) lor (p land q)$ to $p land (neg q lor q)$ does not feel like Distribution, but rather as a kind of 'Un-Distribution' or 'Reverse Distribution', or maybe even 'Taking out a common Factor' ... but it is still called Distribution in logic.
@Bram28 ahh I see, thank you. I've tried to test the result on truth table, and the two expression are indeed equivalent, however, is there a way to prove their equivalency without using truth table? Is it possible to use the distributive law on [(p∧¬q)∨(p∧q)] and arrive at [p∧(¬q∨q)] ? It seems it just goes on forever with the expansion.
– IhavelowIQ
Sep 9 at 0:07
@IhavelowIQ Yes. This is what I tried to say in my Answer: going from $[(p land neg q) lor (p land q)]$ to $[p land (neg q lor q)]$ is using the Distributive Law.
– Bram28
Sep 9 at 0:11
@IhavelowIQ All these laws in Boolean algebra go both ways. For example, using DeMorgan you can go from $neg (p lor q)$ to $neg p land neg q$, but going from $neg p land neg q$ to $neg (p lor q)$ is also using the DeMorgan's law, since the DeMorgan's law is an equivalence. So you can go back and forth using the same law. Same for Distribution.
– Bram28
Sep 9 at 0:14
Oh sorry, I missed your edited message. You are right, I was only thinking of going one way (taught in the book), and [(p∧¬q)∨(p∧q)] to [p∧(¬q∨q)] was definitely not apparent for me. But thanks for clarifying this.
– IhavelowIQ
Sep 9 at 0:15
@IhavelowIQ ok, glad I could help! :)
– Bram28
Sep 9 at 0:16
add a comment |Â
up vote
5
down vote
$$[(colorbluep land lnot q) lor (colorbluep land q)] land q equiv [colorbluep land (colorredlnot q lor q)] land qtagdistributivity$$
$$ equiv (colorbluep land colorred top) land q$$
$$equiv colorbluep land q$$
That is, the distributive law declares that $$[pland (lnot q lor q)] equiv [(p land lnot q) lor (p land q)]$$ That means that it is the same law when we write it: $$[(p land lnot q) lor (p land q)] equiv [pland (lnot q lor q)]$$
Addendum
and if one wants to see why the law is true, truth tables can be really helpful
– The Great Duck
Sep 9 at 4:31
add a comment |Â
2 Answers
2
active
oldest
votes
2 Answers
2
active
oldest
votes
active
oldest
votes
active
oldest
votes
up vote
2
down vote
accepted
The Distributive law goes both ways, because it is an equivalence.
That is, using the Distributive Law you can go from $p land (neg q lor q)$ to $(p land neg q) lor (p land q)$, but you can use that same Distributive Law to go from the latter to the former, and that is what they did here.
I believe the name is somewhat to blame for the fact that so many students, like you, only think of the Distributive Law going one way, because going from $(p land neg q) lor (p land q)$ to $p land (neg q lor q)$ does not feel like Distribution, but rather as a kind of 'Un-Distribution' or 'Reverse Distribution', or maybe even 'Taking out a common Factor' ... but it is still called Distribution in logic.
@Bram28 ahh I see, thank you. I've tried to test the result on truth table, and the two expression are indeed equivalent, however, is there a way to prove their equivalency without using truth table? Is it possible to use the distributive law on [(p∧¬q)∨(p∧q)] and arrive at [p∧(¬q∨q)] ? It seems it just goes on forever with the expansion.
– IhavelowIQ
Sep 9 at 0:07
@IhavelowIQ Yes. This is what I tried to say in my Answer: going from $[(p land neg q) lor (p land q)]$ to $[p land (neg q lor q)]$ is using the Distributive Law.
– Bram28
Sep 9 at 0:11
@IhavelowIQ All these laws in Boolean algebra go both ways. For example, using DeMorgan you can go from $neg (p lor q)$ to $neg p land neg q$, but going from $neg p land neg q$ to $neg (p lor q)$ is also using the DeMorgan's law, since the DeMorgan's law is an equivalence. So you can go back and forth using the same law. Same for Distribution.
– Bram28
Sep 9 at 0:14
Oh sorry, I missed your edited message. You are right, I was only thinking of going one way (taught in the book), and [(p∧¬q)∨(p∧q)] to [p∧(¬q∨q)] was definitely not apparent for me. But thanks for clarifying this.
– IhavelowIQ
Sep 9 at 0:15
@IhavelowIQ ok, glad I could help! :)
– Bram28
Sep 9 at 0:16
add a comment |Â
up vote
2
down vote
accepted
The Distributive law goes both ways, because it is an equivalence.
That is, using the Distributive Law you can go from $p land (neg q lor q)$ to $(p land neg q) lor (p land q)$, but you can use that same Distributive Law to go from the latter to the former, and that is what they did here.
I believe the name is somewhat to blame for the fact that so many students, like you, only think of the Distributive Law going one way, because going from $(p land neg q) lor (p land q)$ to $p land (neg q lor q)$ does not feel like Distribution, but rather as a kind of 'Un-Distribution' or 'Reverse Distribution', or maybe even 'Taking out a common Factor' ... but it is still called Distribution in logic.
@Bram28 ahh I see, thank you. I've tried to test the result on truth table, and the two expression are indeed equivalent, however, is there a way to prove their equivalency without using truth table? Is it possible to use the distributive law on [(p∧¬q)∨(p∧q)] and arrive at [p∧(¬q∨q)] ? It seems it just goes on forever with the expansion.
– IhavelowIQ
Sep 9 at 0:07
@IhavelowIQ Yes. This is what I tried to say in my Answer: going from $[(p land neg q) lor (p land q)]$ to $[p land (neg q lor q)]$ is using the Distributive Law.
– Bram28
Sep 9 at 0:11
@IhavelowIQ All these laws in Boolean algebra go both ways. For example, using DeMorgan you can go from $neg (p lor q)$ to $neg p land neg q$, but going from $neg p land neg q$ to $neg (p lor q)$ is also using the DeMorgan's law, since the DeMorgan's law is an equivalence. So you can go back and forth using the same law. Same for Distribution.
– Bram28
Sep 9 at 0:14
Oh sorry, I missed your edited message. You are right, I was only thinking of going one way (taught in the book), and [(p∧¬q)∨(p∧q)] to [p∧(¬q∨q)] was definitely not apparent for me. But thanks for clarifying this.
– IhavelowIQ
Sep 9 at 0:15
@IhavelowIQ ok, glad I could help! :)
– Bram28
Sep 9 at 0:16
add a comment |Â
up vote
2
down vote
accepted
up vote
2
down vote
accepted
The Distributive law goes both ways, because it is an equivalence.
That is, using the Distributive Law you can go from $p land (neg q lor q)$ to $(p land neg q) lor (p land q)$, but you can use that same Distributive Law to go from the latter to the former, and that is what they did here.
I believe the name is somewhat to blame for the fact that so many students, like you, only think of the Distributive Law going one way, because going from $(p land neg q) lor (p land q)$ to $p land (neg q lor q)$ does not feel like Distribution, but rather as a kind of 'Un-Distribution' or 'Reverse Distribution', or maybe even 'Taking out a common Factor' ... but it is still called Distribution in logic.
The Distributive law goes both ways, because it is an equivalence.
That is, using the Distributive Law you can go from $p land (neg q lor q)$ to $(p land neg q) lor (p land q)$, but you can use that same Distributive Law to go from the latter to the former, and that is what they did here.
I believe the name is somewhat to blame for the fact that so many students, like you, only think of the Distributive Law going one way, because going from $(p land neg q) lor (p land q)$ to $p land (neg q lor q)$ does not feel like Distribution, but rather as a kind of 'Un-Distribution' or 'Reverse Distribution', or maybe even 'Taking out a common Factor' ... but it is still called Distribution in logic.
edited Sep 9 at 0:02
answered Sep 8 at 23:56
Bram28
55.5k33982
55.5k33982
@Bram28 ahh I see, thank you. I've tried to test the result on truth table, and the two expression are indeed equivalent, however, is there a way to prove their equivalency without using truth table? Is it possible to use the distributive law on [(p∧¬q)∨(p∧q)] and arrive at [p∧(¬q∨q)] ? It seems it just goes on forever with the expansion.
– IhavelowIQ
Sep 9 at 0:07
@IhavelowIQ Yes. This is what I tried to say in my Answer: going from $[(p land neg q) lor (p land q)]$ to $[p land (neg q lor q)]$ is using the Distributive Law.
– Bram28
Sep 9 at 0:11
@IhavelowIQ All these laws in Boolean algebra go both ways. For example, using DeMorgan you can go from $neg (p lor q)$ to $neg p land neg q$, but going from $neg p land neg q$ to $neg (p lor q)$ is also using the DeMorgan's law, since the DeMorgan's law is an equivalence. So you can go back and forth using the same law. Same for Distribution.
– Bram28
Sep 9 at 0:14
Oh sorry, I missed your edited message. You are right, I was only thinking of going one way (taught in the book), and [(p∧¬q)∨(p∧q)] to [p∧(¬q∨q)] was definitely not apparent for me. But thanks for clarifying this.
– IhavelowIQ
Sep 9 at 0:15
@IhavelowIQ ok, glad I could help! :)
– Bram28
Sep 9 at 0:16
add a comment |Â
@Bram28 ahh I see, thank you. I've tried to test the result on truth table, and the two expression are indeed equivalent, however, is there a way to prove their equivalency without using truth table? Is it possible to use the distributive law on [(p∧¬q)∨(p∧q)] and arrive at [p∧(¬q∨q)] ? It seems it just goes on forever with the expansion.
– IhavelowIQ
Sep 9 at 0:07
@IhavelowIQ Yes. This is what I tried to say in my Answer: going from $[(p land neg q) lor (p land q)]$ to $[p land (neg q lor q)]$ is using the Distributive Law.
– Bram28
Sep 9 at 0:11
@IhavelowIQ All these laws in Boolean algebra go both ways. For example, using DeMorgan you can go from $neg (p lor q)$ to $neg p land neg q$, but going from $neg p land neg q$ to $neg (p lor q)$ is also using the DeMorgan's law, since the DeMorgan's law is an equivalence. So you can go back and forth using the same law. Same for Distribution.
– Bram28
Sep 9 at 0:14
Oh sorry, I missed your edited message. You are right, I was only thinking of going one way (taught in the book), and [(p∧¬q)∨(p∧q)] to [p∧(¬q∨q)] was definitely not apparent for me. But thanks for clarifying this.
– IhavelowIQ
Sep 9 at 0:15
@IhavelowIQ ok, glad I could help! :)
– Bram28
Sep 9 at 0:16
@Bram28 ahh I see, thank you. I've tried to test the result on truth table, and the two expression are indeed equivalent, however, is there a way to prove their equivalency without using truth table? Is it possible to use the distributive law on [(p∧¬q)∨(p∧q)] and arrive at [p∧(¬q∨q)] ? It seems it just goes on forever with the expansion.
– IhavelowIQ
Sep 9 at 0:07
@Bram28 ahh I see, thank you. I've tried to test the result on truth table, and the two expression are indeed equivalent, however, is there a way to prove their equivalency without using truth table? Is it possible to use the distributive law on [(p∧¬q)∨(p∧q)] and arrive at [p∧(¬q∨q)] ? It seems it just goes on forever with the expansion.
– IhavelowIQ
Sep 9 at 0:07
@IhavelowIQ Yes. This is what I tried to say in my Answer: going from $[(p land neg q) lor (p land q)]$ to $[p land (neg q lor q)]$ is using the Distributive Law.
– Bram28
Sep 9 at 0:11
@IhavelowIQ Yes. This is what I tried to say in my Answer: going from $[(p land neg q) lor (p land q)]$ to $[p land (neg q lor q)]$ is using the Distributive Law.
– Bram28
Sep 9 at 0:11
@IhavelowIQ All these laws in Boolean algebra go both ways. For example, using DeMorgan you can go from $neg (p lor q)$ to $neg p land neg q$, but going from $neg p land neg q$ to $neg (p lor q)$ is also using the DeMorgan's law, since the DeMorgan's law is an equivalence. So you can go back and forth using the same law. Same for Distribution.
– Bram28
Sep 9 at 0:14
@IhavelowIQ All these laws in Boolean algebra go both ways. For example, using DeMorgan you can go from $neg (p lor q)$ to $neg p land neg q$, but going from $neg p land neg q$ to $neg (p lor q)$ is also using the DeMorgan's law, since the DeMorgan's law is an equivalence. So you can go back and forth using the same law. Same for Distribution.
– Bram28
Sep 9 at 0:14
Oh sorry, I missed your edited message. You are right, I was only thinking of going one way (taught in the book), and [(p∧¬q)∨(p∧q)] to [p∧(¬q∨q)] was definitely not apparent for me. But thanks for clarifying this.
– IhavelowIQ
Sep 9 at 0:15
Oh sorry, I missed your edited message. You are right, I was only thinking of going one way (taught in the book), and [(p∧¬q)∨(p∧q)] to [p∧(¬q∨q)] was definitely not apparent for me. But thanks for clarifying this.
– IhavelowIQ
Sep 9 at 0:15
@IhavelowIQ ok, glad I could help! :)
– Bram28
Sep 9 at 0:16
@IhavelowIQ ok, glad I could help! :)
– Bram28
Sep 9 at 0:16
add a comment |Â
up vote
5
down vote
$$[(colorbluep land lnot q) lor (colorbluep land q)] land q equiv [colorbluep land (colorredlnot q lor q)] land qtagdistributivity$$
$$ equiv (colorbluep land colorred top) land q$$
$$equiv colorbluep land q$$
That is, the distributive law declares that $$[pland (lnot q lor q)] equiv [(p land lnot q) lor (p land q)]$$ That means that it is the same law when we write it: $$[(p land lnot q) lor (p land q)] equiv [pland (lnot q lor q)]$$
Addendum
and if one wants to see why the law is true, truth tables can be really helpful
– The Great Duck
Sep 9 at 4:31
add a comment |Â
up vote
5
down vote
$$[(colorbluep land lnot q) lor (colorbluep land q)] land q equiv [colorbluep land (colorredlnot q lor q)] land qtagdistributivity$$
$$ equiv (colorbluep land colorred top) land q$$
$$equiv colorbluep land q$$
That is, the distributive law declares that $$[pland (lnot q lor q)] equiv [(p land lnot q) lor (p land q)]$$ That means that it is the same law when we write it: $$[(p land lnot q) lor (p land q)] equiv [pland (lnot q lor q)]$$
Addendum
and if one wants to see why the law is true, truth tables can be really helpful
– The Great Duck
Sep 9 at 4:31
add a comment |Â
up vote
5
down vote
up vote
5
down vote
$$[(colorbluep land lnot q) lor (colorbluep land q)] land q equiv [colorbluep land (colorredlnot q lor q)] land qtagdistributivity$$
$$ equiv (colorbluep land colorred top) land q$$
$$equiv colorbluep land q$$
That is, the distributive law declares that $$[pland (lnot q lor q)] equiv [(p land lnot q) lor (p land q)]$$ That means that it is the same law when we write it: $$[(p land lnot q) lor (p land q)] equiv [pland (lnot q lor q)]$$
Addendum
$$[(colorbluep land lnot q) lor (colorbluep land q)] land q equiv [colorbluep land (colorredlnot q lor q)] land qtagdistributivity$$
$$ equiv (colorbluep land colorred top) land q$$
$$equiv colorbluep land q$$
That is, the distributive law declares that $$[pland (lnot q lor q)] equiv [(p land lnot q) lor (p land q)]$$ That means that it is the same law when we write it: $$[(p land lnot q) lor (p land q)] equiv [pland (lnot q lor q)]$$
Addendum
edited 2 days ago
answered Sep 9 at 0:07


amWhy
190k26221433
190k26221433
and if one wants to see why the law is true, truth tables can be really helpful
– The Great Duck
Sep 9 at 4:31
add a comment |Â
and if one wants to see why the law is true, truth tables can be really helpful
– The Great Duck
Sep 9 at 4:31
and if one wants to see why the law is true, truth tables can be really helpful
– The Great Duck
Sep 9 at 4:31
and if one wants to see why the law is true, truth tables can be really helpful
– The Great Duck
Sep 9 at 4:31
add a comment |Â
Sign up or log in
StackExchange.ready(function ()
StackExchange.helpers.onClickDraftSave('#login-link');
);
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
StackExchange.ready(
function ()
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f2910203%2fneed-help-simplifying-this-boolean-expression%23new-answer', 'question_page');
);
Post as a guest
Sign up or log in
StackExchange.ready(function ()
StackExchange.helpers.onClickDraftSave('#login-link');
);
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Sign up or log in
StackExchange.ready(function ()
StackExchange.helpers.onClickDraftSave('#login-link');
);
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Sign up or log in
StackExchange.ready(function ()
StackExchange.helpers.onClickDraftSave('#login-link');
);
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Sign up using Google
Sign up using Facebook
Sign up using Email and Password